How Financial Market Development Can Encourage Innovation Activity - Cao, Yu (World Bank, Malaysia, 2021)
Innovation is crucial to improving productivity and fostering sustainable growth, especially among countries that are moving toward or are at the cutting edge of technological advances (technology frontier). Innovation is usually underfinanced due to its high uncertainty nature and market failures caused by mismatches in information about the value of an investment between inventors and outside investors (information asymmetry). The development of financial markets can reduce such frictions and channel financing to innovation. The Brief first examines the recent trend in innovation activities in advanced and emerging markets economies, and then explores the underlying mechanisms through which financial market development may encourage innovation at both the firm and aggregate levels. Lastly, this Brief discusses the relevant policies that can be implemented by policy makers to boost innovation activities.